Formation mechanism of twin structures in p-type (Bi0.25Sb0.75)2Te3 thermoelectric compound. (15th March 2019) - Lee, Kap Ho; Dharmaiah, Peyala; Hong, Soon-Jik
Abstract: The formation mechanism of twin structures in p-type (Bi0.25 Sb0.75 )2 Te3 compound was examined using high-resolution transmission electron microscopy (HR-TEM) and computer simulations. The results shown that the formation of twins is analogous to the twinning mechanism via synchronized activation of Shockley partial dislocations commonly observed terminating {111} growth and annealing twins in face centered cubic (FCC) metals. The 10 1 ¯ 0 boundary, as an incoherent twin boundary (ITB), is mobile due to its lower shear stress compared to that of the coherent {0001} twin boundary; thickness of the twin region can be reduced or increased according to the direction of the movement. Graphical abstract: Unlabelled Image